The Pombaline Reform of secondary studies and its impact on the process of teacher professionalization - Mendonça, Ana Waleska Pollo Campos (2011)
This article analyses the impact of the Pombaline Reform on teacher professionalization process. Pombal’s reforming action on public education helped emerge a state educational system and create, simultaneously, the necessary conditions for its professionalization. Royal teachers of Latin Grammar, Greek, Rhetoric and Philosophy as well as teachers of reading, writing and arithmetic constituted the first two groups of teachers who were selected, hired, paid and controlled by the State. Within this perspective, what makes them a body of professionals is not a corporative understanding of their occupation, but the fact that they were controlled by the state. This work is informed by a socio-historical approach to the teaching profession (Nóvoa, 1987, 1991) aiming primarily at the first group of teachers. The paper focuses on two research questions: study fragmentation and teacher education.